Simple improvements in vector design afford substantial gains in AAV delivery of aggregation-slowing Aβ variants - Ella Borgenheimer; Cameron Trueblood; Bryan L. Nguyen; William R. Lagor; Joanna L. Jankowsky (Elsevier, 2024)
Adeno-associated virus (AAV) gene therapy for neurological disease has gained traction due to stunning advances in capsid evolution for CNS targeting. With AAV brain delivery now in focus, conventional improvements in viral expression vectors offer a complementary route for optimizing gene delivery. We previously introduced a novel AAV gene therapy to slow amyloid aggregation in the brain based on neuronal release of an Aβ sequence variant that inhibited fibrilization of wild-type Aβ. Here we explore three coding elements of the virally delivered DNA plasmid in an effort to maximize the production of therapeutic peptide in the brain. We demonstrate that simply replacing the Gaussia luciferase signal peptide with the mouse immunoglobulin heavy chain signal peptide increased release of variant Aβ by ∼5-fold. Sequence modifications within the expressed minigene further increased peptide release by promoting γ-secretase cleavage. Addition of a cytosolic fusion tag compatible with γ-secretase interaction allowed viral transduction to be tracked by immunostaining, independent from the variant Aβ peptide. Collectively these construct modifications increased neuronal production of therapeutic peptide by 10-fold upon intracranial AAV injection of neonatal mice. These findings demonstrate that modest changes in expression vector design can yield substantial gains in AAV efficiency for therapeutic applications.